In vitro characterization of Trichophyton rubrum and T. mentagrophytes biofilms - Costa-Orlandi, C. B. [UNESP]; Sardi, J. C. O. [UNESP]; Santos, C. T. [UNESP]; Fusco-Almeida, A. M. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Taylor & Francis Ltd, 2014)
Dermatophytes are fungi responsible for a disease known as dermatophytosis. Biofilms are sessile microbial communities surrounded by extracellular polymeric substances (EPS) with increased resistance to antimicrobial agents and host defenses. This paper describes, for the first time, the characteristics of Trichophyton rubrum and T. mentagrophytes biofilms. Biofilm formation was analyzed by light microscopy, scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM) as well as by staining with crystal violet and safranin. Metabolic activity was determined using the XTT reduction assay. Both species were able to form mature biofilms in 72 h. T. rubrum biofilm produced more biomass and EPS and was denser than T. mentagrophytes biofilm. The SEM results demonstrated a coordinated network of hyphae in all directions, embedded within EPS in some areas. Research and characterization of biofilms formed by dermatophytes may contribute to the search of new drugs for the treatment of these mycoses and might inform future revisions with respect to the dose and duration of treatment of currently available antifungals.
Keywords: Trichophyton rubrum; T. mentagrophytes; biofilm; dermatophytes; SEM; CLSM